2020
DOI: 10.1111/obr.13159
|View full text |Cite
|
Sign up to set email alerts
|

Reply to a Letter to the Editor “Is there an exposure–effect relationship between body mass index and invasive mechanical ventilation, severity, and death in patients with COVID‐19? Evidence from an updated meta‐analysis”

Abstract: We thank the authors, Liu et al., for commenting on our paper entitled "Obesity is a risk factor for developing critical condition in COVID-19 patients: A systematic review and meta-analysis" and for updating our analysis. Although their analytical approach was different, and more articles were available at the time of their update, we both concluded that obesity is a risk factor for critical condition in COVID-19 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The contribution of obesity to diseases severity and the requirement of advanced medical care in COVID-19 has been also stated in another initial review that only included three studies [ 78 ]. Our study also further added to a meta-analysis by Földi et al that showed obesity is a risk factor for both ICU admission and mechanical ventilation requirement in COVID-19 patients [ 11 ]. Nevertheless, the study by Földi et al did not investigate the relation of obesity to the risk of mortality, and hospitalization due to COVID-19.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The contribution of obesity to diseases severity and the requirement of advanced medical care in COVID-19 has been also stated in another initial review that only included three studies [ 78 ]. Our study also further added to a meta-analysis by Földi et al that showed obesity is a risk factor for both ICU admission and mechanical ventilation requirement in COVID-19 patients [ 11 ]. Nevertheless, the study by Földi et al did not investigate the relation of obesity to the risk of mortality, and hospitalization due to COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…Heterogeneous findings may be due to low statistical power, small sample size, unified ethnicity, and differences in age and adjustment level for covariates in individual studies. To date, some meta-analyses [ 11 14 ] have attempted to summarize available evidence regarding the relation of obesity to COVID-19 outcomes. Nevertheless, the preliminary meta-analyses included small number of studies, did not comprehensively assess related clinical outcomes, did not assess the influence of potential effect modifiers, such as confounder factors, age, ethnicity and study design, or were conducted on Chinese populations, and thus, were not generalizable to other populations.…”
Section: Introductionmentioning
confidence: 99%